PENGARUH KEDISIPLINAN GURU MENGAJAR TERHADAP PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN AQIDAH AKHLAK DI MIN 1 KOTA BENGKULU - Siti Maruya (IAIN Bengkulu, 2016)
Abstract: This research aims to know: (1) students’ system in a lesson in morals aqidah MIN 1 Bengkulu City? and (2)whether the teacher teaches discipline may influence towards improving student learning outcomes in the belief morallesson in MIN 1 Bengkulu City. This type of research is classified as a field research (field research), using a quantitativeapproach that the data in the form of figures relating to the research theme. To determine the influence of teachersteaching discipline to increased motivation and student learning outcomes in learning Aqidah Morals at MIN 1 Bengkulucity, the authors analyzed using quantitative methods that the formula used is product moment.Based on the data processingand discussion of the results in the previous chapter, it can be concluded that: (1) The level of discipline teachers AqidahMorals in MI country 1 Tanjung Agung is on. category “medium”, and the level of student motivation MI countri 1 TanjungAgung also is in the category “medium”. The discipline of teachers influence on students’ motivation MI countri 1 TanjungAgung, namely in carrying a very high level of influence (the value of the space between 0.800 to 1.000). Thus, disciplineteachers can increase student motivation. (2) The level of discipline teachers Aqidah Morals in MI contri 1 Tanjung Agungin the category “medium”, and the level of student learning outcomes MI 1 countri Tanjung Agung also is in the category“medium”. The discipline of teachers influence on student learning outcomes MI countri 1 Tanjung Agung, which is ineffect a very high level (grades space between 0.800 to 1.000). Thus, discipline teachers can increase student motivation.